Educational inequality and student engagement: an in-depth study of school experiences across social class and track - Kheng, Cameron (Nanyang Technological University, 2024)
Singapore's outstanding educational system has garnered international acclaim, consistently securing top positions in global rankings for standardized tests. However, beneath this veneer of academic excellence lies a more nuanced reality – one of educational inequality intersecting with social class disparities. This thesis delves into these crucial issues by scrutinizing the school experiences of students from different socioeconomic backgrounds and educational tracks (also known as streams) to uncover how they relate to school in highly unequal ways. It draws upon semi-structured interviews with 40 upper secondary school students in Singapore aged 15 to 18. Findings revealed that middle- and upper-class students embraced the importance of education for social advancement, and thus oriented their lives in the pursuit of academic success. Their parents were highly involved in their lives and often marshalled economic and cultural resources to augment their academic growth. In contrast, many working-class students in the lower tracks perceived school as irrelevant to their lives. Their time, talents, and efforts were directed towards alternative goals which they deemed to be more important, i.e., friendships, work, and hobbies. Within these alternative domains, working-class students experienced the success they were deprived from in school. This study challenges the meritocratic view that underperforming students are personally culpable for their failure and calls for an increased recognition that engagement in school is less the result of individual effort but more a product of social class.